Design of ALK Inhibitors for Non-Small Cell Lung Cancer – A Fragment Based Approach - Jain, Anika; James, Nivya; Shanthi, Veerapapillai; Ramanathan, Karuppasamy (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: The increasing cases of non-small cell lung cancer pose a relentless threat to human health. Therefore, using fragment-based drug discovery as the modus operandi, the present study aimed to design small molecule inhibitors for Anaplastic Lymphoma Kinase (ALK) positive Non-Small Cell Lung Cancer (NSCLC) and for its secondary mutation (F1174L). Materials and methods: A total of 12 ALK inhibitors (both FDA and clinical) reported in the literature was utilised in the present study to design the novel and potent ALK inhibitors. Fragment script and BREED of Schrödinger suite was used to generate novel structural combinations. GLIDE algorithm was employed to identify the fragments with high binding affinity to the native and mutant forms of ALK. Screened out fragments were subjected to ADMET analysis. Additionally, the impact of F1174L mutation in the stability of ALK protein was assessed using SDM and I-Mutant tools. RING algorithm was employed to compare the pattern of intramolecular interaction between the native and F1174L ALK protein. Results: A novel hybrid molecule LF16 was identified with better binding, superior CNS activity, higher drug score and low toxicity. Annihilation of intramolecular interactions with Ile 1179, Ile 1170 and Phe1098 were found to be the cause of the destabilizing effect of the mutant protein. Of note, these residues were found to play important roles in the formation of F-core as well as in stabilizing αC-helix, which is important for maintaining the inactive form of ALK. Moreover, Conclusion: We believe that these results could foster the designing and development of novel ALK inhibitors towards the management of crizotinib resistance in the near future.
Keywords: ALK; SDM; I-Mutant; RIN; GLIDE; ADMET